Source-based tasks in academic writing assessment: Lexical diversity, textual borrowing and proficiency. Issue 24 (December 2016) - Gebril, Atta; Plakans, Lia
Abstract: With the growing interest in integrating reading with writing to assess academic English writing, several questions have been raised about the role of source vocabulary in test takers' writing and, consequently, how scores from these tasks should be interpreted. The current study investigates issues related to the influence of textual borrowing on lexical diversity and the difference in lexical diversity across test scores on integrated tasks. To this end, 130 students in a Middle Eastern university completed a reading-based integrated task. The essays were analyzed for lexical diversity using CLAN software, a computer program developed to compute lexical diversity. Then to illuminate the impact of the source texts, vocabulary originating from the reading were removed from the essays, and the D index was recomputed for a lexical diversity score with borrowed vocabulary omitted. A paired samples t -test and Analysis of Variance (ANOVA) were used to answer the research questions. The results showed that borrowing from source texts significantly affects the lexical diversity values in integrated writing. Further, the results demonstrated that lexical diversity plays a substantial role in integrated writing scores. Highlights: The study investigates the influence of textual borrowing on lexical diversity. The D index was used to compute lexical diversity. The results showed textual borrowing affecting lexical diversity. Lexical diversity affects integrated writing scores.